KETERLIBATAN ISTRI NELAYAN DALAM MENAMBAH PENGHASILAN KELUARGA DI KELURAHAN PASIE NAN TIGO KOTA PADANG - Wirdatul' Aini (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
The research aimed at describing the involvement of anglers’ wives in helping the family income at Pasie Nan Tigo Padang. The research discussed several aspects related to the observed variable. They were: (1) the underlying reasons why the wives helped the family income; (2) the roles of the wives seen from their profile, educational background; (3) how the anglers’ wives helped the family income. The design of the research was qualitative research; a case study. This research described what happened in the field naturally. It was about the involvement of anglers’ wives in helping the family income at Pasie Nan Tigo Padang. The focus of the research was how far the involvement was done. The data were obtained by using snowball sampling technique. The data was validated through triangulation. Data was obtained from the women who worked to help the family income, and from the neighborhood who knew the women or the subject of the research. Research findings showed: (1) the purpose of the anglers’ wives working to add the family income were to help fulfilling the family needs, (2) the anglers’ wives worked for four up to eight hours a day, even more, most of them were graduated from elementary school, junior and senior high school. The research suggested that the anglers’ wives should have various skills so that they could live in a better condition, and it was expected that the government developed micro business for them.